A framework for allocating fishing rights in small-scale fisheries. (1st July 2019) - Smith, Sarah L.; Battista, Willow; Sarto, Nicole; Fujita, Rod; Stetten, Denise Choy; Karasik, Rachel; Burden, Merrick
Abstract: The FAO Voluntary Guidelines for Securing Small-Scale Fisheries have called out the need to provide secure tenure rights as a means of securing livelihoods, promoting food security, and poverty alleviation, all of which can support the human rights of small-scale fishers. However, there are few examples to be found in the literature of the necessary processes and mechanisms for allocating such rights to small-scale fishers. While in industrial fisheries the criteria for allocation are typically based on catch history data, these are likely to be unavailable for many small-scale fisheries, which will instead require different criteria for making decisions. Furthermore, as linked social-ecological systems providing both livelihoods and food to fishing communities, as well as playing important social and cultural roles, small-scale fisheries are likely to have allocation goals that differ from industrial fisheries. These may include promoting equity, preserving cultural values, ensuring the participation of marginalized groups, or setting aside fish for subsistence, among others. A process for allocating rights will require extensive stakeholder participation to elucidate these underlying goals and values and to develop solutions that best address them. This paper describes the steps necessary for engaging stakeholders in such a process and provides examples of novel fisheries allocation mechanisms that may address the concerns of small-scale fisheries. Highlights: Limited data and social/cultural concerns make allocation decisions complex in SSFs. We present a stepwise, participatory process for allocating fishing rights in a SSF. Setting allocation-relevant goals to guide decision-making is critical. Allocation systems should be developed by stakeholders based on goals and values. We provide example allocation methods to meet sociocultural goals with limited data.